NORMA-NORMA HUKUM HAK ASASI MANUSIA DALAM AL-QURAN: STUDI KRITIS ATAS TAFSIR AL-QURAN SURAT AL-NISÂ’ AYAT 135 - Deni Kamaludin Yusup (Asy-Syari'ah, 2015)
This paper is simply explaining on the legal norms of human rights in the Quran through critical study on the Quranic interpretation Surah al-Nisâ’ verse 135. As the primary source of Islamic law, the Quran is believed covered the various verses which are relevant with the legal norms of human rights. Moreover the guarantee of human rights and its consideration in the Quran has been presently existed more than the idea of human rights in Western world. In addition, the crucial proble here is not talking about accepting or rejecting human rights within the Quran, but many scholars find the difficulties on understanding human rights in the Quran more than accepting it as the Holy Book and the way of life for human beings.